STUDY OF IRON ÃâÃâ TIN BEHAVIOUR IN SMELTING PROCESS STAGE II AT PT. TIMAH - PRATAMA (NIM : 12105037); Pembimbing : Dr. Zulfiadi Zulhan, ST., MT., ADRIAN
Tin smelting process at PT. Timah consist of two stages, concentrate smelting (smelting process stage I) and slag smelting (smelting process stage II). Tin iron with high purity and slag that still consist 20 - 30% of Sn produced in concentrate smelting. Slag that produced in concentrate smelting goes to smelting process stage II in order to recover the tin metal from the slag of stage process I. The product of smelting process stage II is an alloy of iron Ã‚Â– tin metal (hardhead) that still contain iron relatively high (30 Ã‚Â– 50%) and slag. In this final assignment, Fe and Sn behavior in slag and melt is researched by make variation increment of anthracite and limestone to get high degree of Sn in hardhead. The influence of increment of limestone to slag composition, slag basicity, slag viscosity, and ratio of γ(SnO)/γ(FeO) in the slag is the main objectivity of this final assignment. The distribution coefficient of Sn Ã‚Â– Fe in slag and melt (k) in the increment of anthracite and limestone determined from the campaign of smelting process stage II at PT. Timah. The variation increment of limestone is 60 Kg, 70Kg, 80 Kg, and 85 Kg per ton tin, while the variation increment of anthracite is 150 Kg, 160 Kg, and 170 Kg per ton tin. The smelting process operate at temperature 1450oC using the reverberatory furnace. The result of the research show that the increment of limestone may reduced the viscosity of slag in addition to increase the basicity of slag. The higher basicity in slag, the higher ratio of γ(SnO)/γ(FeO) we can get. The higher ratio of γ(SnO)/γ(FeO) can reduced the degree of SnO in slag. Coeeficient distribution of Sn Ã‚Â– Fe (k) in smele and slag can be increased by increment of limestone. The increment of anthracite as a reduction agent can make the reduction atmosphere increased so that the SnO and FeO degree in slag reduced, however, the conclusion whether the increment of anthracite can increase the recovery of slag cannot be known yet from 3 data variation increment of anthracite.